Islam, Religious Confrontation and Hoaxes in the Digital Public Sphere: Comparison of Bangladesh and Indonesia - Al-Zaman, Md. Sayeed; Alimi, Moh Yasir (Komunitas, 2021)
Religion has a considerable contribution to the creation of present Bangladesh and Indonesia. Historically, religious communalism is common in these two regions and its presence is visible to date. Like other countries, both countries are moving more toward digitalization with a good number of digital migrants, making the internet a digital public sphere. Like offline society, online is now becoming a place of religious dakwah and contentions as well. Digital space offers both opportunities and challenges for the democratic religious public sphere. This article discusses the similarity and differences of online religious public spheres between Indonesia and Bangladesh. The research was conducted in 2021 observing social media particularly Facebook. This research finds that the online religious public sphere witnesses online piety, religious deliberation, the spread of religious hoaxes, and Islamism. While in Bangladesh, online disinformation leads to religious communalism and offline violence against religious minorities, in Indonesia, the digital public sphere is largely dominated by religious discourses argumentation among Muslims and the rise of post-Islamism. The online public sphere of both countries similarly witnesses the rise of hoaxes, post-truth, and banal religion.